The Composition and Nature of Vulcanisation Fumes in the Rubber Industry – a Technical Review. Issue 4 (November 2015) - Forrest, Martin
A comprehensive review of the published literature has been undertaken to achieve a thorough assessment and understanding of rubber fumes. This review has made apparent the fact that rubber fumes are not a single chemical entity, but have a very complex chemical composition which varies according to a number of factors. In addition to providing data on the individual chemical substances that are present in rubber fumes, a description is given of their different physical forms (i.e. gas and aerosol), their potential sources within the rubber compounds (e.g. volatile ingredients) and the factors (e.g. process temperature and specific processing operation) that affect their composition and physical form. This review has also shown how changes in the rubber industry and rubber technology over the past 40 years have altered the composition and level of rubber fumes and increased the level of protection for workers. Also included are recent developments in the field, such as the international standard ISO/TS 17796:2013 qualitative method for the identification of substances in rubber fumes. By carrying out analytical work using such methods, and having knowledge of the factors that affect the composition of rubber fumes, it is possible obtain a reasonable understanding of their chemical composition on a case by case basis.